Challenges of leadership : C E O exchange - Greenfield, Jeff (Films Media Group, 2001)
Jeff Greenfield, uses in-depth intervew with internationally recognized and respected CEOs to shed light on those managerial,organizational, and technological issues that are shaping the marketplace of ideas. in addition, this comrehensive business library also explores the personal side of commerce that shape and influence their businessphilosophies,strategies, and decisions.